2017
DOI: 10.1007/s00423-017-1616-3
|View full text |Cite
|
Sign up to set email alerts
|

The combination of mitomycin-induced blood cells with a temporary treatment of ciclosporin A prolongs allograft survival in vascularized composite allotransplantation

Abstract: The findings of this study show that the combination of MICs with a temporary CsA treatment significantly prolongs the rejection-free interval in a complex VCA model. The combination of MICs with CsA showed no adverse events such as graft-versus-host disease. MICs, which are generated by a simple and reliable in vitro technique, represent a potential therapeutic tool for prolonging allograft survival through immunomodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
1
10
0
3
Order By: Relevance
“…A limitation of this study is the absence of surveillance biopsies beyond day 7 after transplantation to rule out alloimmune injury such as subclinical T cell-mediated inflammation. CyA was chosen rather than tacrolimus, because it represented the standard calcineurin inhibitor for unsensitized kidney recipients in our center at the time of the study, and since no interference of CyA with MIC treatment was found during preclinical experiments (26). We speculate that tacrolimus would provide similar results.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is the absence of surveillance biopsies beyond day 7 after transplantation to rule out alloimmune injury such as subclinical T cell-mediated inflammation. CyA was chosen rather than tacrolimus, because it represented the standard calcineurin inhibitor for unsensitized kidney recipients in our center at the time of the study, and since no interference of CyA with MIC treatment was found during preclinical experiments (26). We speculate that tacrolimus would provide similar results.…”
Section: Discussionmentioning
confidence: 99%
“…They further extended these results from sorted DCs to whole PBMC in both rat and porcine contexts with improved graft survival with mitomycin C treated PBMC infusion ( 46 ). They also showed improved survival in a vascular composite allograft context in rats ( 47 ). Recently, they completed a trial in humans where they showed both safety of MICs derived from whole PBMC as well as specific inhibition of donor responses in patients treated with MICs ( 48 ).…”
Section: Dst Using Modified Cellular Productsmentioning
confidence: 97%
“…Die Feststellung, dass die MICs nur in der Spender-Haut, jedoch nicht im Muskel eine verstärkte Immunreaktion hervorriefen, unterstreicht die Bedeutung des Gewebetyps und damit der Vielzahl von Faktoren, die in diesem Modell mitspielen. Im Rahmen einer vorangegangenen Studie konnte bei intraoperativer Gabe damit eine Potenzierung der immunsuppressiven Wirkung erreicht werden [16]. Im Gegensatz zur Applikation von MICs führte die präoperative Gabe unbehandelter Spender-PBMCs nicht zu einer beschleunigten Immunantwort.…”
Section: Diskussionunclassified
“…Im Rahmen der erstmaligen Applikation von MICs in einem experimentellen VCA-Modell konnten wir eine signifikante immunsuppressive Wirkung durch die systemische Applikation von MICs am Transplantationstag im Rattenmodell zeigen [14]. In Folgestudien führte sowohl die lokale, intramuskuläre Applikation von MICs als auch die Kombination aus systemischer MIC-Therapie und temporärer Immunsuppression im komplexen VCA-Modell zu einer signifikant späteren Abstoßungsreaktion und damit Potenzierung der immunsuppressiven Wirkung [15,16]. Nachdem die präoperative Applikation von MICs bei Herztransplantationen im Rattenmodell Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
Section: Introductionunclassified
See 1 more Smart Citation